A systematic review of the impact of person‐centred care interventions on the behaviour of staff working in dementia care. (27th November 2019) - Blake, Daniel; Berry, Katherine; Brown, Laura J. E.
Abstract: Aim: To examine the content, focus, and effectiveness of person‐centred care (PCC) interventions aimed at increasing staff PCC behaviour in health and social care settings for people with dementia. Design: Systematic search and narrative synthesis of quantitative data. Data sources: PsychINFO, Medline, EMBASE, Web of knowledge, CINAHL, ASSIA, and BNI were searched from inception to 5 November 2016. Review methods: All records retrieved were screened using predetermined eligibility criteria. Quality assessment was performed with the Effective Public Health Practice Project tool (EPHPP). Results: A total of 4, 367 records were screened and 33 studies examining the impact of PCC interventions were included. Eight different categories of PCC intervention were identified, with seven of these having at least some evidence to support their effectiveness in increasing staff PCC behaviour. Conclusion: The range of interventions and outcome measures identified in this review highlight different ways PCC behaviour can be demonstrated by staff and the range of interventions that can be used to enhance PCC staff behaviour. In future, more rigorously controlled research comparing the relative effectiveness of these interventions will support nursing facilities and staff to choose appropriate interventions to support them in enhancing PCC. Impact: This study addressed the health priority of increasing PCC for people with dementia. It found preliminary evidence that seven of the eight intervention types identified are effective at increasing staff PCC behaviour in health and social care settings for people with dementia. Abstract : 目的: 研究以人为本的护理干预措施的内容、重点和有效性, 期以改善以人为本的护理人员在痴呆症患者保健和社会护理环境中的行为。 设计: 定量数据采用系统搜索法和叙述性综合法。 数据来源: 通过 PsycINFO、Medline、EMBASE、知识网、CINAHL、ASSIA 和 BNI数据库进行检索(从建立之初到2016年11月5日)。 评估方法: 使用预先确定的合格标准对检索到的所有记录进行筛选。通过使用有效公共卫生实践项目工具(EPHPP)展开质量评估。 结果: 共筛选了4, 367条记录, 并纳入了33项调查发现, 用于研究以人为本的护理干预措施的影响。最后确定了8种不同类别的以人为本的护理干预措施, 其中有7种措施可在一定程度上证明能有效改善以人为本的护理人员的行为。 结论: 本次评估研究所确定的一系列干预措施和成果措施突出了护理人员展示以人为本的护理行为的不同方式, 以及可用于加强以人为本的护理人员行为的干预措施的范围。今后, 对这些干预措施的相对有效性展开更为严格的对照研究, 将有助于护理机构和护理人员选择适当的干预措施, 从而帮助他们提高以人为本的护理疗效。 影响: 本项研究针对改善痴呆症患者以人为本的护理的保健优先事项进行了探讨。初步证据表明, 在已确定的8种干预措施类型中, 有7种可有效改善以人为本的护理人员在痴呆症患者保健和社会护理环境中的行为。